Management of generalized severe periodontitis using full‐mouth disinfection and systemic antibiotics in a leukemic patient before stem cell transplantation: A case report. Issue 2 (3rd December 2020) - Morikawa, Satoru; Tsunoda, Kazuyuki; Miyashita, Yoko; Nasu, Mana; Horie, Nobuyuki; Usuda, Sho; Kato, Jun; Mori, Takehiko; Nakagawa, Taneaki
Abstract: The full‐mouth disinfection protocol implemented in this case can be integrated into established protocols for treating severe periodontitis in the context of a hematological malignancy, without any interference with the cancer treatment. Abstract : The full‐mouth disinfection protocol implemented in this case can be integrated into established protocols for treating severe periodontitis in the context of a hematological malignancy, without any interference with the cancer treatment.